A new genus for the Blackfin Sucker, Thoburnia atripinnis (Cypriniformes: Catostomidae) - Armbruster, Jonathan W. (Zootaxa, 2024)
Thoburnia atripinnis is more closely related to Hypentelium (hogsuckers) than it is to other Thoburnia, and its presence in the Barren River of Kentucky is disjunct from that of true Thoburnia. Its unique morphology is unlike that of the easily recognized hogsuckers, making placement of the species within Hypentelium untenable; thus, a new genus is described. The new genus can be separated from all other catostomids by the presence of thin, black, prominent stripes on the body, a large black mark on the anterodist al portion of the dorsal fin, presence of pads ventrally on the leading portion of the pectoral fin, lateral laminae of the dermethmoid angled anteriorly, and the base of the lateral ethmoid narrow.